Expanding the Neuroimaging Phenotype of Neuronal Ceroid Lipofuscinoses - Biswas, A.; Krishnan, P.; Amirabadi, A.; Blaser, S.; Mercimek-Andrews, S.; Shroff, M. (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: Neuronal ceroid lipofuscinoses are a group of neurodegenerative disorders characterized by the accumulation of autofluorescent lipopigments in neuronal cells. As a result of storage material in the brain and retina, clinical manifestations include speech delay, cognitive dysfunction, motor regression, epilepsy, vision loss, and early death. At present, 14 different ceroid lipofuscinosis (CLN) genes are known. Recently, the FDA approved the use of recombinant human proenzyme of tripeptidyl-peptidase 1 for CLN2 disease, while phase I/IIa clinical trials for gene therapy in CLN3 and CLN6 are ongoing. Early diagnosis is, therefore, key to initiating treatment and arresting disease progression. Neuroimaging features of CLN1, CLN2, CLN3, and CLN5 diseases are well-described, with sparse literature on other subtypes. We aimed to investigate and expand the MR imaging features of genetically proved neuronal ceroid lipofuscinoses subtypes at our institution and also to report the time interval between the age of disease onset and the diagnosis of neuronal ceroid lipofuscinoses.MATERIALS AND METHODS: We investigated and analyzed the age of disease onset and neuroimaging findings (signal intensity in periventricular, deep, and subcortical white matter, thalami, basal ganglia, posterior limb of the internal capsule, insular/subinsular regions, and ventral pons; and the presence or absence of supratentorial and/or infratentorial atrophy) of patients with genetically proved neuronal ceroid lipofuscinoses at our institution. This group consisted of 24 patients who underwent 40 brain MR imaging investigations between 1993 and 2019, with a male preponderance (male/female ratio = 15:9).RESULTS: The mean ages of disease onset, first brain MR imaging, and diagnosis of neuronal ceroid lipofuscinoses were 4.70 extpm 3.48 years, 6.76 extpm 4.49 years, and 7.27 extpm 4.78 years, respectively. Findings on initial brain MR imaging included T2/FLAIR hypointensity in the thalami (n = 22); T2/FLAIR hyperintensity in the periventricular and deep white matter (n = 22), posterior limb of the internal capsule (n = 22), ventral pons (n = 19), and insular/subinsular region (n = 18); supratentorial (n = 21) and infratentorial atrophy (n = 20). Eight of 9 patients who had follow-up neuroimaging showed progressive changes.CONCLUSIONS: We identified reported classic neuroimaging features in all except 1 patient with neuronal ceroid lipofuscinoses in our study. CLN2, CLN5, and CLN7 diseases showed predominant cerebellar-over-cerebral atrophy. We demonstrate that abnormal signal intensity in the deep white matter, posterior limb of the internal capsule, and ventral pons is more common than previously reported in the literature. We report abnormal signal intensity in the insular/subinsular region for the first time. The difference in the median time from disease onset and diagnosis was 1.5 years.CLNceroid lipofuscinosisDWMdeep white matterIQRinterquartile rangeI-SIinsular/subinsular regionNCLneuronal ceroid lipofuscinosesPLICposterior limb of the internal capsulePVWMperiventricular white matterSCWMsubcortical white matter